(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
An ear infection is among the common diseases in children. There is an increased rate of antimicrobial resistance to pathogens that cause ear infections worldwide. We analyzed two years of data on bacterial isolates associated with suspected cases of ear infection and their antibiotic-resistant patterns. All records on ear swabs (n= 134) sent for culture and sensitivity, at the medical microbiology laboratory of a tertiary Health Facility in Northeastern Nigeria, from 2017 to 2018 were reviewed. The patients’ socio-demographic information, bacteria isolated, antibiotics tested, and their sensitivity patterns were extracted. Kirby-Bauer method of antibiotic sensitivity testing and CLSI guidelines were adopted. Descriptive analyses of the data were conducted. Of a total of 134 patients’ records extracted 50.7% were female, median age 12 (IQR 9-15 years). Of the 134 samples cultured, 124 (92.5%) yield bacterial growth. Eight (8) different isolates obtained were Staphylococcus aureus (38.7%), Pseudomonas aeruginosa (17.7%), Proteus mirabilis (16.1%) Proteus vulgaris (9.7%), Klebsiella oxytoca (9.0%), Klebsiella pneumoniae (5.6%) Escherichia coli (2.4%) and Enterococcus spp. (0.8%), Staphylococcus aureus was the predominant isolate, while Enterococcus spp. was the least. A high resistant rate was recorded against many of the antibiotics tested. All isolate demonstrated resistance to amoxicillin and cotrimoxazole, and high sensitivity to ciprofloxacin. Staphylococcus aureus and Pseudomonas aeruginosa were the most common pathogens isolated. Most isolates showed high sensitivity to ciprofloxacin. The high resistance rate recorded on most of the antibiotics tested highlight the need for appropriate prescription of antimicrobials based on local susceptibility profile in the treatments of ear infection.